The renegotiation and revision of legal transaction as the new remedies in the contracts for works: a solution to the problem of the unpredictable risks from comparative approach - Buendía De Los Santos, Eduardo (2016)
In terms of the works contracts as a general rule the target prices between the parties are immutable. However, in the execution of the contracts for works might well emerge unforeseeable events, which would produce costs to the contractor. To these events, what actions the parties migth take? What kind of remedies does the Peruvian Civil Code offer?. In this article, the autor analizes these issues and proposes solutions to these unforeseeable risks, all on the basis of Peruvian Civil Code and a comparative study with Italian Civil Code.